HI View of the Norma Galaxy Cluster with MeerKAT - Mophahlane, Koketso Vincent (Rhodes University, Faculty of Science, Department of Physics and Electronics)
Studies reveal that galaxies assemble into clusters as gas-rich, active star-forming disks and eventually settle in the virialized core as quenched early-type galaxies with depleted gas. To examine environmental effects responsible for the quenched population in the cluster core, we exploit the higher sensitivity of the MeerKAT telescope to probe Hi properties of galaxies in the Norma cluster. The Norma cluster is an ideal laboratory for this study since it is a rich and massive cluster of nearby galaxies. The Hi data cube used covers a velocity range of 483 âˆ’ 11, 113 km/s, with a noise rms sensitivity of 0.09 mJy/beam and an angular resolution of âˆ¼ 14.65"²"² Ã— 9.28"²"². A total of 25 reliable Hi sources were detected over the entire velocity range. The Hi detections reveal two major galaxy overdensities located at vrad âˆ¼ 2096 âˆ’ 7646 km/s and vrad âˆ¼ 10, 000 km/s. The first is associated with the Norma cluster gravitational potential and indicates a substructure in its velocity distribution; the other is a population of background galaxies. In this work, the Norma cluster has 13 cluster members detected in Hi and 130 galaxies from optical surveys. The spatial distribution of cluster members covers a field that is 2/3 Ã— RA, where RA = 2.02 Mpc at cz = 4871 km/s. From the spatial distribution, optical galaxies are densely populated in the central regions, while most galaxies in Hi were detected on the outskirts. From the phase-space diagram, 6 galaxies detected in Hi are found in the virialised region, while the rest of the detections are infalling for the first time. Hi detections that are not yet virialised have asymmetrical morphologies, while virialised detections have truncated gas disks. Most cluster members that were found to have asymmetrical gas disks are also Hi deficient by 0.8 âˆ’ 1.2 dex but show excess SFR efficiency for the amount of Hi detected. The results demonstrate that the initial phase of galaxy-ICM interactions might be responsible for morphological transformation and enhancement of star formation activity.
Keywords: Norma Cluster; MeerKAT; Galaxies -- Motion in line of sight; Galaxies -- Clusters; Star formation